2016
DOI: 10.2147/ijgm.s92404
|View full text |Cite
|
Sign up to set email alerts
|

Association between sarcopenia and quality of life in quilombola elderly in Brazil

Abstract: IntroductionCurrently, there is no single consensual definition of sarcopenia in the literature. This creates a challenge for the evaluation of its prevalence and its direct or indirect impact on the quality of life of elderly populations of different races and ethnicities. Furthermore, no studies as yet have analyzed these variables in populations of elderly subjects of the “quilombola” ethnic group.ObjectiveWe aimed to verify the association between sarcopenia and quality of life in quilombola elderly using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 39 publications
0
14
0
1
Order By: Relevance
“…Muscle mass was measured using BIA (n=9), DXA (n=7), CT images (n=3), or magnetic resonance imaging (n=1). Higher muscle mass and not having sarcopenia was positively associated with serum albumin levels (149) better physical function (150159), higher quality of life (157, 159), and longer survival (154, 160162). Higher muscle mass was also negatively associated with cardiovascular disease risk factors (163), idiopathic pulmonary fibrosis (154), low bone mineral density (164), bone fractures (165), hospitalization (161), poor pulmonary function (166); sarcopenia was associated with poorer disease specific outcomes such as ankylosing spondylitis (164) and poor renal function (167).…”
Section: Outpatient Settingsmentioning
confidence: 99%
“…Muscle mass was measured using BIA (n=9), DXA (n=7), CT images (n=3), or magnetic resonance imaging (n=1). Higher muscle mass and not having sarcopenia was positively associated with serum albumin levels (149) better physical function (150159), higher quality of life (157, 159), and longer survival (154, 160162). Higher muscle mass was also negatively associated with cardiovascular disease risk factors (163), idiopathic pulmonary fibrosis (154), low bone mineral density (164), bone fractures (165), hospitalization (161), poor pulmonary function (166); sarcopenia was associated with poorer disease specific outcomes such as ankylosing spondylitis (164) and poor renal function (167).…”
Section: Outpatient Settingsmentioning
confidence: 99%
“…For instance, cross-sectionally, lower educational attainment was associated with a greater likelihood of sarcopenia in 730 Italian community-dwelling adults aged ≥ 65 years, 10 but not in 70 Quilombola persons aged ≥ 60 years from Brazil. 11 Lower household income and lower educational attainment may predispose populations to lower skilled occupations, which includes manual labour and repetitive exposures; however, lower functional capacity would increase the difficulty of performing job requirements with ease and without injury. Should socially disadvantaged individuals be at a disproportionately greater risk of sarcopenia, this would also have significant implications for primary prevention, diagnosis and management.…”
Section: Introductionmentioning
confidence: 99%
“…Two studies identified sarcopenia through the skeletal muscle index 18,19 . One study used muscle cross-sectional area 17 , and another study used the SARC-F (sluggishness, assistance in walking, rise from a chair, climb stairs, falls) questionnaire 13 . Another study applied the algorithm of the European Working Group for Sarcopenia in Older People (EWGSOP) 21 .…”
Section: Resultsmentioning
confidence: 99%
“…QoL is defined by the World Health Organization as an individual's acuity in life in relation to their culture and value systems and relative to their goals, expectations, standards, and concerns 9 . Despite the increasing interest in studying sarcopenia, limited studies have focused on sarcopenia among the hospitalized elderly [10][11][12][13][14] . This could be because, sarcopenia has been inconsistently defined or determined as various outcome measures have been applied to different settings for the elderly population.…”
mentioning
confidence: 99%
See 1 more Smart Citation